Direct measurement of groundwater flux in aquifers within the discontinuous permafrost zone: an application of the finite volume point dilution method near Umiujaq (Nunavik, Canada) - Jamin, Pierre; Cochand, Marion; Lemieux, Jean-Michel; Dagenais, Sophie; Fortier, Richard; Brouyère, Serge; Molson, John W. H. (Hydrogeology Journal, 2020)
Permafrost thaw is a complex process resulting from interactions between the atmosphere, soil, water and vegetation. Although advective heat transport by groundwater at depth likely plays a significant role in permafrost dynamics at many sites, there is lack of direct measurements of groundwater flow patterns and fluxes in such cold-region environments. Here, the finite volume point dilution method (FVPDM) is used to measure in-situ groundwater fluxes in two sandy aquifers in the discontinuous permafrost zone, within a small watershed near Umiujaq, Nunavik (Quebec), Canada. The FVPDM theory is first reviewed, then results from four FVPDM tests are presented: one test in a shallow supra-permafrost aquifer, and three in a deeper subpermafrost aquifer. Apparent Darcy fluxes derived from the FVPDM tests varied from 0.5 × 10−5 to 1.0 × 10−5 m/s, implying that advective heat transport from groundwater flow could be contributing to rapid permafrost thaw at this site. In providing estimates of the Darcy fluxes at the local scale of the well screens, the approach offers more accurate and direct measurements over indirect estimates using Darcy’s law. The tests show that this method can be successfully used in remote areas and with limited resources. Recommendations for optimizing the test protocol are proposed.